2018
DOI: 10.3390/biom8040159
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Bile Acids Signaling and Perspective on the Signal of Ursodeoxycholic Acid, the Most Hydrophilic Bile Acid, in the Heart

Abstract: Bile acids (BA) are classically known as an important agent in lipid absorption and cholesterol metabolism. Nowadays, their role in glucose regulation and energy homeostasis are widely reported. BAs are involved in various cellular signaling pathways, such as protein kinase cascades, cyclic AMP (cAMP) synthesis, and calcium mobilization. They are ligands for several nuclear hormone receptors, including farnesoid X-receptor (FXR). Recently, BAs have been shown to bind to muscarinic receptor and Takeda G-protein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 127 publications
1
65
0
Order By: Relevance
“…The most common secondary bile acids, resulting from deconjugation and dehydroxylation of primary bile acids, are desoxycholic acid (DCA) and lithocholic acid (LCA) [23]. Due to its hydrophobicity, reabsorption rates into the enterohepatic circulation are small for LCA [24]. On the other hand, DCA is reabsorbed in the colon and accumulates in the bile acid pool [17].…”
Section: Bile Acid Metabolism and Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The most common secondary bile acids, resulting from deconjugation and dehydroxylation of primary bile acids, are desoxycholic acid (DCA) and lithocholic acid (LCA) [23]. Due to its hydrophobicity, reabsorption rates into the enterohepatic circulation are small for LCA [24]. On the other hand, DCA is reabsorbed in the colon and accumulates in the bile acid pool [17].…”
Section: Bile Acid Metabolism and Chemistrymentioning
confidence: 99%
“…The amphiphilic character of bile acids is explained by their rigid steroid backbone containing methyl groups oriented towards a hydrophobic face, whereas the hydroxyl groups and the amino group (taurine or glycine) are oriented towards a hydrophilic face [25]. Due to their varying hydroxylation, bile acids differ in hydrophobicity, which decreases in the order of LCA > DCA > CDCA > CA [24]. By the action of anaerobic microbiota, primary bile acids are converted into secondary and tertiary bile acids.…”
Section: Bile Acid Metabolism and Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…BS and BA have a wide range of functions, from emulsification of dietary lipids, and facilitating their digestion and absorption, to signal transduction in cell proliferation, metabolism, and differentiation [27]. As a direct mode of action, BS form mixed micelles, which aids in the absorption of lipolysis products and lipid-soluble vitamins.…”
Section: Physiological Function Of Bsmentioning
confidence: 99%
“…However, the fermentation of dietary fibres by the gut microbiota may partly liberate the bound BAs and the drop in pH that is associated with the fermentation process decreases the activity of the enzyme 7 α-dehydroxylase which catalyses the conversion of primary to secondary BAs [21]. While some secondary BAs like DCA or LCA have been associated with negative effects on health [22] others like UDCA show beneficial effects [23,24]. In our study, we observed a significant decrease in total BA under the oatmeal treatment as compared to the control treatment, similar like it was reported by Gunness et al in pigs [25].…”
Section: Discussionmentioning
confidence: 99%